Alkali-activated fly ash cured with pulsed microwave and thermal oven: A comparison of reaction products, microstructure and compressive strength. (April 2023) - Shi, Shi; Li, Hui; Zhou, Qizhi; Zhang, Hongzhou; Basheer, P.A.M.; Bai, Yun
Abstract: The reaction products and microstructure of an 8 M NaOH-activated fly ash (AAFA) cured with microwave and thermal oven curing were comparatively investigated. The results show that the formation of an Al-rich N-A-S-H gel with a flaky morphology and crystalline chabazite-Na between fly ash particles were favoured under the microwave curing, whilst a Si-rich N-A-S-H gel with a fibrilllar morphology and crystalline hydroxysodalite on the surface of fly ash particles were dominant under the thermal oven curing. The formation of these unique reaction products and microstructure under the microwave curing is attributed not only to the thermal effect of microwaves which can increase the temperature of AAFA volumetrically, but also to the non-thermal effects of microwaves which can promote the dissolution and diffusion of silica and alumina during the AAFA reaction process. This explains why AAFA can achieve a high early strength within a short period of microwave curing.